Winter Money - Plattner, Andy (Book collections on Project MUSE., 1997)
The ten stories in Winter Money are set in rural Kentucky and West Virginia, in dim horse racing and river towns. The men in Andy Plattner's stories are tough and uncertain, the women independent and disappointed, but they are strong-willed and high-spirited, always believing there's a better life, just over the horizon, after the next race. The title story depicts the life of a jockey agent who has seen some bad breaks but knows in his heart he can turn things around if he can just get some ""winter money"" to make a fresh start in Florida. In ""Chandelier, "" a bankrupt horse breeder risks ev